Unlocking the potential: advancements and applications of gene therapy in severe disorders - Rahul G. Ingle; Gehan M. Elossaily; Mohd Nazam Ansari; Shivani Makhijani (Annals of Medicine)
Introduction Several severe disorders, such as inherited diseases (e.g. cystic fibrosis and beta thalassemia), genetic diseases (e.g. malignant tumors and diabetes), and infectious diseases (e.g. HIV) are pose significant challenges to human health.Background Over the past few decades, researchers have been working on gene therapies, and currently, terrible dreams have come true. To date, the Food and Drug Administration (FDA) has approved multiple gene therapies such as Kynamro for familial hypercholesterolaemia, Exondys51 for duchenne muscular dystrophy, Spinraza for spinal muscular atrophy, etc., rest for cancer, infectious diseases, and rare diseases.Discussion The authors have summarized recent advances in gene therapy, its background, molecular basis (e.g. viral and non-viral vectors), gene-editing techniques (e.g. CRISPR/Cas9, TALEN, ZFN), and its foremost applications in severe disorders, such as cancer, monogenic disorders (e.g. spinal muscular atrophy), polygenic disorders (e.g. autism), neurogenic disorders (e.g. Parkinson disease and Alzheimer’s disease), and infectious diseases (e.g. HIV).Challenges In addition, we explored the major challenges faced by gene therapies during targeted delivery, immunogenicity, efficacy, and safety.Conclusion To date, most of the promising approaches, such as different vectors, target cell populations, and both in vivo and ex vivo have paved the foundation for applications of gene therapies. Additionally, advances in enhancing the immune system that would certainly lower the healthcare costs. This review highlights the translatory potential of gene therapy in revolutionizing the treatment landscape for severe disorders.